Diversity of Species and Conservation Priority of Butterfly at Suranadi Natural Park of West Lombok, Indonesia - Ilhamdi, Mohammad Liwa; Idrus, Agil Al; Santoso, Didik (Biosaintifika: Journal of Biology & Biology Education, 2018)
Butterflies play an important role in the ecosystem of Suranadi Natural Park in West Lombok. Butterflies help preserving the existence and diversity of flora by facilitating the process of pollination so it is crucial for flowering plants. The present study aimed at analyzing the diversity and determining the priority of butterfly conservation at Suranadi Natural Park of West Lombok. This exploration is a descriptive study. Data were observed in four-time repetition in the morning and in the afternoon for two months. The sweeping net technique following observation path was employed in this research (line left, line right, Â line central and line waterway). The data analysis used the Shannon-Wiener diversity index and priority for conservation determined by Ministry of Forestry Regulation Number: P.57 / Menhut-II / 2008. Fourty (40) species of butterflies belonging to 5 families identified. The diversity index (H ) of butterflies ranges from 2.63 to 3.43 (medium-high). The two species of the Papilionidae family found at TWA Suranadi, namely, Troides helena and Papilio memnon were the priority of conservation. This research would be helpful to consider conservation strategy and ecotourism.